Proceedings Of The International Conference On Rohotics, Vision. Information and Signal Processing - Tan , Kuan Liung; Ngah, Umi Kalthum (2003)
Unprocessed mammograms and ultrasound images are sometimes difficult to assess through the naked eye. Images that are inflicted with degradations due to overexposure. inadequate lighting or faulty electronic imaging equipment can be rendered useful through the process of image restoration. Degradations such as defocus or various types of noises can be removed and thus made more suitable for interpretations in the medical field. For this purpose, a software package named Image Restoration 2 (IR2) was developed.